Systemic immune changes associated with adjuvant interferon-α2b-therapy in stage III melanoma patients. Issue 4 (August 2015) - Chevolet, Ines; Schreuer, Max; Speeckaert, Reinhart; Neyns, Bart; Hoorens, Isabelle; van Geel, Nanja; Krüse, Vibeke; Hennart, Benjamin; Allorge, Delphine; Van Gele, Mireille; Brochez, Lieve
<x xml:space="preserve">Abstract</x> Interferon-α (IFN-α) is the only approved adjuvant treatment for high-risk melanoma patients in Europe, but the impact on overall survival is low. Although it is believed that IFN-α exerts its effects through immunomodulation, data on its impact on circulating immune cells are scarce. Flow cytometry was performed on peripheral blood mononuclear cells of eight IFN-α2b-treated stage III melanoma patients and 26 untreated stage III melanoma patients as controls to enumerate myeloid and plasmacytoid dendritic cells (mDC and pDC), monocytic and polymorphonuclear myeloid-derived suppressor cells (mMDSC and pmnMDSC) and cytotoxic and regulatory T-cells (Tregs). The expression of several immunosuppressive markers [indoleamine 2, 3-dioxygenase (IDO), programmed-death ligand-1 (PD-L1) and cytotoxic T-lymphocyte antigen-4 (CTLA4)] was explored. IDO activity in the blood was confirmed by ultra-performance liquid chromatography. Compared with controls, IFN-α2b treatment was associated with increased IDO expression by pDCs (P=0.021) and an increased kynurenine/tryptophan ratio in the serum (P=0.004), compatible with IDO enzyme activity. Furthermore, IFN-α2b-treated patients had a decreased mDC/DC ratio (P=0.002), decreased CD3+ lymphocytes (P=0.034) and increased circulating Treg (P<0.001) and PD-L1+cytotoxic T-cell (P=0.001) frequencies. IDO expression is upregulated in circulating pDCs of high-risk melanoma patients treated with adjuvant IFN-α2b. This is associated with tryptophan consumption in the patients' serum and higher Treg and PD-L1+cytotoxic T-cell frequencies. We hypothesize that in IFN-α2b-treated patients, IDO activity acts as a negative feedback mechanism and might limit the clinical efficacy of IFN-α2b therapy. The underlying mechanism should be explored as this could lead to more efficient immunotherapies.